EVALUATION OF ORGANIC MULCH ON THE GROWTH AND YIELD OF SUGARCANE (Saccharum officinarum L.) IN A SOUTHERN GUINEA SAVANNAH OF NIGERIA - M. Ahmed; K. P. Baiyeri; B. C. Echezona (Journal of Animal and Plant Sciences, 2014)
Sustainability in crop production could be achieved using agricultural wastes which litter the environment to ameliorate crop soils. The effect of organic mulches on the growth and yield of two sugar cane varieties (NCS 008 and Bida local) was therefore evaluated during 2010 (plant crop) and 2011 (ratoon crop) at Badeggi (90 03ꞌN, 060 09ꞌE; altitude 89 m a.s.l.) Nigeria. Mulch materials (rice husk and groundnut shell) were each applied at the rates of 0, 20 and 40 tonnes ha-1 in a factorial experiment laid out in a randomised complete block design (RCBD), with three replications. The variety NCS 008 produced significantly (p<0.05) higher number of tillers, stalk length, yield and chewable stalks in both the regular and ratoon crops relative to the local. The establishment count of NCS 008 was higher compared to Bida local (73% vs. 38%) in the ratoon and vice versa in the plant crop. Mulching with groundnut shell produced significantly (p<0.05) higher establishment count and stalk lengths compared to rice husk mulch for the ratoon crops, but did not differ appreciably in the main (plant) crop. Irrespective of the cropping system, stalk girth, tiller count, chewable stalks and yield were significantly (p < 0.05) higher with groundnut shell compared with rice husk mulch. Aside from establishment count, which had an inverse relationship with mulching rate in the plant crop, all the other traits assessed had a direct relationship with mulching rate in the two systems. The interaction effect of variety x organic mulch x organic mulch rate were also significant (p<0.05) for both the plant and ratoon crops on most of the parameter considered.
Keywords: Agricultural waste; chewing and industrial cane; cropping system; regular and ratoon crops